Perencanaan Pendidikan Dengan Metode Man Power Planing Approach - Rima Erviana; Siti Qomariyah; Rubi Babullah; Nazrul Zimatul Rizky; Siti Nurafifah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Educational planning is an important aspect in developing an effective and efficient education system. In this era of globalization, an innovative approach is needed to meet the need for a qualified workforce. One method that can be used in educational planning is the Man Power Approach method. The Man Power Approach method is an approach that involves analyzing future workforce needs, competencies, and developing a curriculum that is relevant to the job market. By using the Man Power Approach method in educational planning, it is hoped that we can create an education system that is responsive to workforce needs and capable of producing quality graduates who are ready to face the challenges of the world of work.